2022
DOI: 10.3390/antibiotics11081048
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Modification and Structure-Activity Study of GL-29, an Analogue of the Antimicrobial Peptide Palustrin-2ISb

Abstract: Antimicrobial peptides (AMPs) are considered as promising antimicrobial agents due to their potent bioactivity. Palustrin-2 peptides were previously found to exhibit broad-spectrum antimicrobial activity with low haemolytic activity. Therefore, GL-29 was used as a template for further modification and study. Firstly, the truncated analogue, GL-22, was designed to examine the function of the ‘Rana box’, which was confirmed to have no impact on antimicrobial activity. The results of antimicrobial activity assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This is consistent with the blue fluorescence of DAPI and the absence of PI in untreated cells, since PI cannot penetrate intact bacterial membranes. These findings are comparable with studies, such as [63] by Liu et al, where GL-22 and GL-29 peptides showed damage against S. aureus by a membranolytic mechanism suggested by fluorescence microscopy. On the other hand, it has been observed that bacteria exposed to peptides tend to cluster together, a characteristic event previously described due to instability caused by the reduced membrane potential [64].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the blue fluorescence of DAPI and the absence of PI in untreated cells, since PI cannot penetrate intact bacterial membranes. These findings are comparable with studies, such as [63] by Liu et al, where GL-22 and GL-29 peptides showed damage against S. aureus by a membranolytic mechanism suggested by fluorescence microscopy. On the other hand, it has been observed that bacteria exposed to peptides tend to cluster together, a characteristic event previously described due to instability caused by the reduced membrane potential [64].…”
Section: Discussionsupporting
confidence: 91%
“…Such AMPs maximizes the role of targeted identification of infection sites and targeted killing of pathogenic bacteria while maintaining the homeostasis of the microflora and the health of tissue cells. [21] Targeted AMPs can be constructed in various ways and can be used to target lipopolysaccharides (LPS) to kill specific gram-negative bacteria. For example, Muhle et al constructed a cysteine 𝛽-fold framework to mimic the binding site of LPS and designed the resulting AMP sequence and its derivatives to have a significant bactericidal effect on gramnegative bacteria antimicrobial activity was 200-fold higher than that of gram-positive bacteria.…”
Section: Targeted Amp Designmentioning
confidence: 99%
“…Such AMPs maximizes the role of targeted identification of infection sites and targeted killing of pathogenic bacteria while maintaining the homeostasis of the microflora and the health of tissue cells. [ 21 ] Targeted AMPs can be constructed in various ways and can be used to target lipopolysaccharides (LPS) to kill specific gram‐negative bacteria. For example, Muhle et al.…”
Section: Abdominal Infectionmentioning
confidence: 99%